Effect of temperature of oxalic acid on the fabrication of Porous anodic alumina from Al-Mn alloys - Mohd Nazree, Derman, Dr. (Hindawi Publishing Corporation, 2014)
Link to publisher's homepage at http://www.hindawi.com/